Novel miRNA-based drug CD5-2 reduces liver tumor growth in diethylnitrosamine-treated mice by normalizing tumor vasculature and altering immune infiltrate - Liu, Ken; Chen, Jinbiao; Zhao, Yang; Boland, Jade; Ting, Ka Ka; Lockwood, Glen; McKenzie, Catriona; Kench, James; Vadas, Mathew A.; Gamble, Jennifer R.; McCaughan, Geoffrey W. (Frontiers in Immunology, 2023)
Introduction Liver cancers exhibit abnormal (leaky) vasculature, hypoxia and an immunosuppressive microenvironment. Normalization of tumor vasculature is an emerging approach to treat many cancers. Blockmir CD5-2 is a novel oligonucleotide-based inhibitor of the miR-27a interaction with VE-Cadherin, the endothelial-specific cadherin. The combination of a vasoactive medication with inhibition of immune checkpoints such as programmed cell death protein 1 (PD1) has been shown to be effective in treating liver cancer in humans. We aimed to study the effect of CD5-2 combined with checkpoint inhibition (using an antibody against PD1) on liver tumor growth, vasculature and immune infiltrate in the diethylnitrosamine (DEN)-induced liver tumor mouse model. Methods We first analyzed human miR-27a and VE-Cadherin expression data from The Cancer Genome Atlas for hepatocellular carcinoma. CD5-2 and/or anti-PD1 antibody were given to the DEN-treated mice from age 7-months until harvest at age 9-months. Tumor and non-tumor liver tissues were analyzed using histology, immunohistochemistry, immunofluorescence and scanning electron microscopy. Results Human data showed high miR-27a and low VE-Cadherin were both significantly associated with poorer prognosis. Mice treated with CD5-2 plus anti-PD1 antibody had significantly smaller liver tumors (50% reduction) compared to mice treated with either agent alone, controls, or untreated mice. There was no difference in tumor number. Histologically, tumors in CD5-2-treated mice had less leaky vessels with higher VE-Cadherin expression and less tumor hypoxia compared to non-CD5-2-treated mice. Only tumors in the combination CD5-2 plus anti-PD1 antibody group exhibited a more favorable immune infiltrate (significantly higher CD3+ and CD8+ T cells and lower Ly6G+ neutrophils) compared to tumors from other groups. Discussion CD5-2 normalized tumor vasculature and reduced hypoxia in DEN-induced liver tumors. CD5-2 plus anti-PD1 antibody reduced liver tumor size possibly by altering the immune infiltrate to a more immunosupportive one.